2021
DOI: 10.1073/pnas.2019524118
|View full text |Cite
|
Sign up to set email alerts
|

Diverse innate stimuli activate basophils through pathways involving Syk and IκB kinases

Abstract: Mature basophils play critical inflammatory roles during helminthic, autoimmune, and allergic diseases through their secretion of histamine and the type 2 cytokines interleukin 4 (IL-4) and IL-13. Basophils are activated typically by allergen-mediated IgE cross-linking but also by endogenous “innate” factors. The aim of this study was to identify the innate stimuli (cytokines, chemokines, growth factors, hormones, neuropeptides, metabolites, and bacterial products) and signaling pathways inducing primary basop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 66 publications
(99 reference statements)
0
24
0
5
Order By: Relevance
“…Consistent with this, preincubating DRG neurons with the JAK2-specific inhibitor AG490 (10 μM) did not influence the inhibitory effect of IL-33 on I A (decrease of 30.9 ± 4.2%, Figure 3 C). It has been demonstrated that Syk is a nonreceptor tyrosine kinase involved in several cytokine signaling pathways 42 , 43 . Immunoblot analysis of DRG cell lysates revealed the protein expression of Syk (Figure 3 D & Figure S5 ), and immunofluorescence staining showed that Syk was coexpressed with ST2 (Figure 3 B).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this, preincubating DRG neurons with the JAK2-specific inhibitor AG490 (10 μM) did not influence the inhibitory effect of IL-33 on I A (decrease of 30.9 ± 4.2%, Figure 3 C). It has been demonstrated that Syk is a nonreceptor tyrosine kinase involved in several cytokine signaling pathways 42 , 43 . Immunoblot analysis of DRG cell lysates revealed the protein expression of Syk (Figure 3 D & Figure S5 ), and immunofluorescence staining showed that Syk was coexpressed with ST2 (Figure 3 B).…”
Section: Resultsmentioning
confidence: 99%
“…These receptors are highly expressed by epithelial cells that are present in the lungs and gastrointestinal tract. Several innate stimuli including epithelial derived inflammatory cytokines (IL-33, IL-18, Thymic stromal lymphopoietin, and GM-CSF), growth factors (IL-3, IL-7, TGF-β, and VEGF) activate the mouse basophils ( 57 ). Also, airway epithelial cell line A549 has been reported to induce activation of human basophils ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various T cells subsets are found in acute wounds and are responsible for bacterial elimination, modulation of immune responses and tissue remodeling. Basophils are one of the first cells that infiltrate into the injured tissue attracted by endogenous factors, such as IL-33, IL-18, thymic stromal lymphopoietin (TSLP), granulocytemacrophage colony-stimulating factor (GM-CSF), IL-3, IL-7, TGF-β, VEGF and IFN type I [43]. They are the major producers of IL-4, the cytokine which is known to facilitate fibroblast proliferation and chemotaxis as well as the production of collagen and ECM molecules in skin wounds [44,45].…”
Section: Acute Wound Healingmentioning
confidence: 99%